Design of reduced graphene hydrogel with alkylamine surface functionalization through immersion/agitation method and its adsorption mechanism - Lim, Alvin Teik Zheng; Boonyuen, Supakorn; Li, Gan Yen; Lim, Hong Ngee; Andou, Yoshito (Elsevier, 2021)
To date, existing methods for graphene functionalization entail complex procedures, hence efficient and facile methods are desired. In this study, alkylamine functionalization on reduced graphene hydrogel (rGH) was achieved via a facile two-step method involving hydrothermal treatment of graphene oxide (GO) to rGH followed by the immersion/agitation treatment of the rGH in octylamine (OA), decylamine (DA) and dodecylamine (DDA). It was found that the interactions of the alkylamine occurred via the epoxy ring-opening and amidation. To emphasize the advantage of this method, the adsorption kinetics on methylene blue (MB) and bisphenol-A (BPA) was further accessed. Shorter alkyl chain alkylamine (OA & DA) functionalized rGHs showed improvement in their adsorption capacity due to the increase in the specific surface area of the hydrogels. The highest specific surface area was obtained for rGH-DA at 47.80 m2/g followed by rGH-OA (47.37 m2/g), rGH-DDA (42.00 m2/g) and rGH (27.29 m2/g). However, longer chain alkyl chain alkylamine (DDA) functionalized rGHs showed lower adsorption capacity posited from the crowding of long alkyl chain which decreases the π–π interactions between the MB/BPA and the graphene sheets. rGH-DA exhibited the highest adsorption capacity for MB and BPA at 482 and 228 mg/g, respectively. In addition, the alkylamine functionalized hydrogels showed high regeneration behaviour after three cycles of adsorption-desorption: above 85% and 75% for MB and BPA, respectively. This proposed facile functionalization route will open interesting possibilities in the design of novel reduced graphene-based based hydrogels with improved adsorption performance that can bring ample benefits in wastewater remediation.